Involvement of Young People in Extracurricular Activities in General Education Secondary School – an Opportunity for their Balanced Development - TŁUCZEK-TADLA, EWA (Journal of Education, Technology and Computer Science, 2023)
The article addresses important issues related to the daily educational experiences of Polish secondary school students. In the first place it focuses on the general concepts conveyed by the title, such as balanced development, extracurricular activities, and volunteering. The theoretical and exploratory purpose as well as practical and implementation related goals have been formulated. The main research problem was defined as follows: What was secondary school students’ involvement in extracurricular activities in school, in the context of their opportunities for balanced development? The study applied a method of diagnostic assessment, a survey technique and a specially designed questionnaire. The survey was conducted in May and June 2022 among 286 secondary school students in the Podkarpackie Region. Majority of the respondents did not engage in extracurricular activities. The students who were involved in some kind of extracurricular activity most often perceived various gains for themselves. The most popular were volunteering projects organised by the school. The students reported that involvement in extracurricular activities most often allowed them to gain knowledge, develop skills and help other people. The gains perceived by the respondents can contribute to their balanced development.